2014
DOI: 10.1007/s00226-014-0683-7
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication, material properties, and application of bamboo scrimber

Abstract: In this study, mechanical fluffing, thermal treatment, and phenol formaldehyde (PF) impregnation, as well as cold-in and cold-out hot-pressing processes, were used to fabricate bamboo scrimbers. The water absorption, dimensional stability, and mechanical properties of the bamboo scrimbers were determined. The bamboo scrimber made from bamboo bundles processed at 180°C hot dry air treatment combined with 18 % PF resin loading showed good technological properties. This bamboo scrimber had improved water absorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
72
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(72 citation statements)
references
References 15 publications
(10 reference statements)
0
72
0
Order By: Relevance
“…To date, bamboo anatomy and property research has gradually formed into an organized, standardized, and systematic entity. Technologies for slicing bamboo veneer, fabrication of bamboo flooring, laminate, glulam, and engineered materials are becoming mature (Yu et al 2015).…”
Section: Wood-based Panelsmentioning
confidence: 99%
“…To date, bamboo anatomy and property research has gradually formed into an organized, standardized, and systematic entity. Technologies for slicing bamboo veneer, fabrication of bamboo flooring, laminate, glulam, and engineered materials are becoming mature (Yu et al 2015).…”
Section: Wood-based Panelsmentioning
confidence: 99%
“…Bamboo scrimber has a standard shape and relatively low variability in material properties. Furthermore, bamboo is a rich, renewable, and widespread resource in Latin America and Asia . Bamboo scrimber is becoming an increasingly attractive structural material in construction engineering.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the density had a significant influence on the mechanical and water absorption properties of bamboo scrimber. Yu et al [8] investigated the use of bamboo as a promising raw material for fabricating bamboo scrimbers. Their study aimed to determine the water absorption, dimensional stability, and mechanical properties of bamboo scrimbers with different weight percentages of phenol formaldehyde resin and different heat treatments of bamboo bundles.…”
Section: Introductionmentioning
confidence: 99%